ANALISIS KELIMPAHAN UDANG GALAH (Macrobrachium rosenbergii) DI SUNGAI MENDUK KABUPATEN BANGKA - Bobby Fajrilian (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2018)
Menduk River is a river located in Menduk Village, Mendo Barat, Bangka District. Abundance is used to measure and calculate the number of lobster that found in menduk river. It can describe the potential level of lobster present in the Menduk River. The purpose of this study is to calculate the abundance of catches of lobster and to know the parameters of physics and chemistry on menduk river then Analyze the relationship of physical and chemical factors of waters to the abundance of catches lobster. Determination of research station is done by using method of purposive sampling with correlation coefficient analysis. The catch of Galah Udang on March 11 tails and 9 tails in April. The highest correlation coefficient value of water temperature is 0.95 and the lowest value is pH 0.14. The results show that most temperatures influence the catch compared to other physical and chemical parameters.